"Good" news from nowhere: imagining utopian sustainable accounting. Issue 5 (15th June 2015) - Atkins, Jill; Atkins, Barry Colin; Thomson, Ian; Maroun, Warren
Abstract : Purpose: – The purpose of this paper is to attempt to provide a ray of hope, in the form of a Morris-style utopian dream of a sustainable world, as a basis for new forms of accounting and accountability in contemporary society. Design/methodology/approach: – The method is four-fold, weaving together an auto-ethnographic approach, a contextual dialogue between accounting academics and lobbyists, a Morris-inspired utopian metaphor and a stakeholder accountability event in the form of oral disclosures written as a song cycle. Findings: – Current efforts at integrated reporting are unlikely to change how large companies do business in order to address the risk of climate change in the short term. If the UN reports on climate change are correct, the authors need to take immediate action. The authors argue that, instead of waiting for climatic disaster to lead to a paradigm shift in corporate practice, "monetisation" of the costs of climate change is one way to encourage integrated thinking and sustainable business models. This relies on existing finance and accounting discourse to create a new "field of environmental visibility" which engenders environmental awareness on the part of the world's companies and policy makers. Practical implications: – This utopian image may not appear a practicable, realistic solution to current problems but represents a starting point for optimism. It provides inspiration for policy makers to develop better forms of sustainability reporting, more suitable to the accelerating rates of climatic change. Originality/value: – To the authors' knowledge this is the first attempt to develop Morris's News From Nowhere as a basis for building new forms of accounting and accountability.